Diel activity rhythms in wild songbirds in the Subarctic - Staurland, Marie Østlid (UiT Norges arktiske universitet, 2024)
The highly rhythmic environment caused by the rotation of the earth has driven the evolution of an intrinsic timekeeping mechanism in most organisms known as circadian clocks. As climate change drives the expansion of southern species into northern latitudes, their circadian clocks are challenged by the novel light conditions they encounter. In contrast to the clear day and night in southern latitudes, the light-dark regime of the Arctic environment is characterised by a reduced daily amplitude of solar illumination, including periods where the sun remains continuously below (polar night) and above (polar day) the horizon, and rapid changes in daylength in between. This may lead to disruption of the circadian organisation with consequence of correct timing of behaviour. Here we observed the diel activity rhythms of three wild songbird species, the great tit, blue tit, and willow tit, which have colonised northern latitudes at different times. Daily activity was obtained through foraging activity using camera traps. We observed a distinct difference in diel activity rhythms between the newer coloniser, great and blue tit, from the well-established species, willow tit, of northern areas during polar day and polar night. We observed an activity pattern similar to a relative coordination for the great and blue tit population during polar night, which may suggest times of circadian disruption. In contrast, willow tit maintains robust entrainment throughout the year. Overall, our observation may indicate distinct differences in circadian clock properties between the populations, which may related to the time they have colonised the northern latitudes. Willow tits ability to maintain entrained when the daily amplitude of solar illumination is reduced suggest that the circadian system is more sensitive to light cues as an adaption to the light regime in the Arctic.